Towards a Social Realist Framework for Analyzing Academic Advising in Global South Contexts - NAYAGER, ANESHREE; DE KLERK, DANIE (Journal of International Students, 2023)
Academic advising is a proven high-impact practice, shown to have the potential to help increase students’ prospects of academic success, increase their sense of belonging and integration at their institution of higher learning, and provide unique insights into the lived realities and experiences of higher education students. For this reason, advising can be seen as a transformative activity within the student support space in South African higher education institutions. As a practice and profession, advising has existed in the Global North (GN) for decades. However, in South Africa – a developing country in the Global South (GS) – academic advising remains a nascent field. Consequently, the overarching ideas that inform academic advising in the South African context (both theoretically and practically), tend to be drawn predominantly from the GN and more developed countries. The unchallenged acceptance and tacit dominance of theoretical perspectives and practices from these countries can be considered problematic.